IDENTIFIKASI KOMPONEN UTAMA MINYAK ATSIRI DAUN UJUNG ATAP (Baeckea frutescens L.) DAN UJI AKTIVITAS ANTIBAKTERI TERHADAP BAKTERI Escherichia coli IDENTIFICATION OF MAIN COMPONENTS OF LEAF TIP ESSENTIAL OIL (Baeckea frutescens L.) AND ANTIBACTERIAL ACTIVITY TEST AGAINST Escherichia coli BACTERIA - Eka Wahyuni; M Agus Wibowo; Ajuk Sapar (Indonesian Journal of Pure and Applied Chemistry, 2022)
Baeckea frutescens L is a tropical plant that usually grows in coastal areas. Its leaves resemble needles with trees that resemble large pines. Baeckea frutescens L can be found in various regions in Indonesia, one of which is in Nanjung Village, Ketapang Regency, and West Kalimantan. Baeckea frutescens L essential oil was obtained by isolation using steam distillation. The results obtained from the isolation of the essential oil of Baeckea frutescens L was a yield of 0.0037% (v/v) and a density of 0.874 g/mL. Baeckea frutescens L essential oil was then analyzed using GC-MS. The results of the analysis showed that there were 32 compounds, with the main compounds being -ocimene, eucalyptol, -myrcene, -humulene, -terpineol. The results of the antibacterial activity test against Escherichia coli bacteria, concentrations of 5% (15.9 mm), 2.5% (15.6 mm), 1.25% (12.9 mm) and 0.625% (11.8 mm).